The life-history of basalt ground stone tools from early urban domestic contexts: A chronicle from the EBA III of Tell es-Safi/Gath, Israel. (2016) - , Jeremy A. Beller; , Haskel J. Greenfield; , Itzhaq Shai; Maeir, Aren M.
No abstract available